Transient Electronics: Dry Transient Electronic Systems by Use of Materials that Sublime (Adv. Funct. Mater. 12/2017). (March 2017) - Kim, Bong Hoon; Kim, Jae‐Hwan; Persano, Luana; Hwang, Suk‐Won; Lee, Seungmin; Lee, Jungyup; Yu, Yongjoon; Kang, Yongseon; Won, Sang M.; Koo, Jahyun; Cho, Youn Kyoung; Hur, Gyum; et al.
Abstract : By using subliming materials, Bong Hoon Kim, John A. Rogers, and co‐workers successfully design dry electronic systems that undergo timed self‐destruction. As described in article number 1606008, sublimation causes mechanical fragmentation and disintegration of the devices. The concept is promising for such diverse fields as biomedical implants, environmental monitoring, and secure data systems.